Analisis sajian LKS fisika kelas X semester 1 terkait komponen higher order thinking skills (HOTS) - Suryani Fadhilah; Silvi Yulia Sari; Yenni Darvina; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2020)
The 2013 curriculum requires teachers to encourage students to think at a higher level and possess higher-order thinking skills known as Higher Order Thinking Skills (HOTS). To achieve this the teacher must consciously and continuously practice using learning strategies with an orientation to training students to think at a higher level. This relates to the learning components that must be prepared by the teacher such as learning models, learning media, and teaching materials. One of the aids for students is teaching materials in the form of worksheets. This research is a descriptive study with a qualitative approach. The population of data in this study is the entire semester X semester I high school physics textbook used by 23 schools in West Sumatra. Sampling was done by purposive sampling technique. The sample in this study was the highest school physics class X 1-semester worksheet used by schools published by two different publishers and four worksheets made by Physics teachers in the school where the worksheet was used. The data in this study were taken using LKS presentation analysis instruments and data collection techniques through documentation studies. Based on the research that has been done, it can be concluded that the Analysis conducted on the Physics Worksheets for Class X Senior High School Semester I related to the availability of HOTS components obtained the results of the analysis that LKS who obtained a percentage with the fullness of indicators on the highest HOTS component namely LKS made by high school subject teachers 12 Padang 39%. Whereas the Physics Worksheet that received a percentage of the fulfillment of indicators on the lowest HOTS component was the Worksheet published by CV Grahadi 14%.